Legislative power in the Republic of Poland - M. I. Marchuk (Law and Safety)
The article is focused on the problems of studying the constitutional and legal aspects of the functioning of the bicameral parliament in the Republic of Poland. The research is carried out with the aim of studying and scientific understanding of the practical implementation of certain aspects of bicameralism in Ukraine.